2020
DOI: 10.3892/ol.2020.12261
|View full text |Cite
|
Sign up to set email alerts
|

7‑dehydrocholesterol suppresses melanoma cell proliferation and invasion via Akt1/NF‑κB signaling

Abstract: Melanoma is the most lethal cutaneous cancer with a high metastatic rate worldwide, causing ~55,500 deaths annually. Although the selective B-Raf oncogene serine/threonine-kinase (BRAF) inhibitors, dabrafenib and vemurafenib, have been approved for the treatment of BRAF-mutant metastatic melanoma, the 5-year survival rate remains unfavorable due to acquired therapy resistance. Therefore, it is of great importance to develop alternative therapeutic drugs and uncover their mechanisms for the treatment of melanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…However, this scientific area is quite poorly studied and further, we focus on the direct or indirect involvement of cholesterol precursors in cancers. We found that cholesterol precursors can be formally divided into three groups ( Table 4 ) depending on their impact on carcinogenesis [ 50 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this scientific area is quite poorly studied and further, we focus on the direct or indirect involvement of cholesterol precursors in cancers. We found that cholesterol precursors can be formally divided into three groups ( Table 4 ) depending on their impact on carcinogenesis [ 50 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intermediate metabolites of cholesterol have been demonstrated various functions in tumorigenesis. We and others previously showed that 7-dehydrocholesterol and vitamin K3 inhibited melanoma cell proliferation and induce apoptosis via AKT/MAPK signaling pathways [51][52][53]. while Nelson et al found that cholesterol metabolite 27-HC, as a partial agonist for the estrogen receptor and the liver X receptor, promoted tumor growth and metastasis in mouse models of mammary cancer [24].…”
Section: Discussionmentioning
confidence: 89%
“…For the cirReNET we built, there were many targeted genes involved in the mechanism of tumor genesis, such as AKT1 ( Liu et al, 2020 ), ErbB2 ( Li et al, 2018a ), ITGB7 ( Sun et al, 2020 ), BAX, MAPK, FBXL12 ( Nita et al, 2016 ), CCL7 ( Zhang et al, 2020b ) and so on. These genes also play very important roles in cell proliferation, apoptosis, movement, T-cell differentiation, adhesion, and polarity formation.…”
Section: Discussionmentioning
confidence: 99%